Neurocognitive deficits after botulism: a clinical case series study - Rosenqvist, Laura; Sandvei, Charlotte; Skarphedinsson, Sigurdur (Frontiers in Neurology, 2024)
Purpose: This case study examined long-term cognitive deficits after botulism. Only a very limited number of studies on post-acute cognitive impairment after botulism exist, and data is incomplete. Method: A semi-structured interview on long-term cognitive consequences of botulism was conducted for six family members, who contracted the infection after ingestion of lumpfish-roe 2.5 years ago. Two of the family members underwent neuropsychological assessment on attention, memory, and executive functioning as well. Finding: Results of the semi-structured interviews showed individual subjective cognitive deficits across processing speed, attention, concentration, short-and long-term memory, and executive functioning. Test results showed mild cognitive impairment in attention and mild-moderate deficits in executive functioning. Conclusion: These results support previous findings that patients of various infectious diseases may suffer unspecific long-term neurocognitive deficits. Assessment and initiation of relevant post-acute treatment and rehabilitation might be central to prognosis, functional ability, and psychological well-being.